UPAYA PENINGKATAN DIPLOMASI PUBLIK INDONESIA DI NEGARA-NEGARA ASEAN MELALUI BEASISWA SENI DAN BUDAYA INDONESIA (BSBI) - Dina Suryadi; Sumiati FisipHI (Global Mind, 2019)
AbstractThis paper analyzes how Indonesian Art and Culture Scholarship (IACS) becomes aninstrument to improve Indonesian public diplomacy in ASEAN. The Ministry of ForeignAffairs of the Republic of Indonesia has organized the IACS program since 2003. Startingfrom the ASEAN Community’s ratification program in 2015, Indonesia must adjust its publicdiplomacy in ASEAN region. This paper applies concept of public diplomacy to look atvarious efforts to improve Indonesian public diplomacy in ASEAN and national interest toanalyze why Indonesia uses public diplomacy in achieving Indonesia's national interests. Byorganizing the IACS program, Indonesia has purpose to introducing Indonesian art andculture to the people of ASEAN countries so that it can improve its public diplomacy andencounter new challenges from the ASEAN Community.Keywords: ASEAN Community, Indonesian Arts and Cultural Scholarship, Ministry ofForeign Affairs of the Republic of Indonesia.